Surge Capacity: Analysis of Census Fluctuations to Estimate the Number of Intensive Care Unit Beds Needed. (15th July 2014) - Olafson, Kendiss; Ramsey, Clare; Yogendran, Marina; Fransoo, Randall; Chrusch, Carla; Forget, Evelyn; Garland, Allan
<x xml:space="preserve">Abstract</x> Objective To compare methods of characterizing intensive care unit (ICU) bed use and estimate the number of beds needed. Study Setting Three geographic regions in the Canadian province of Manitoba. Study Design Retrospective analysis of population‐based data from April 1, 2000, to March 31, 2007. Methods We compared three methods to estimate ICU bed requirements. Method 1 analyzed yearly patient‐days. Methods 2 and 3 analyzed day‐to‐day fluctuations in patient census; these differed by whether each hospital needed to independently fulfill its own demand or this resource was shared across hospitals. Principal Findings Three main findings were as follows: (1) estimates based on yearly average usage generally underestimated the number of beds needed compared to analysis of fluctuations in census, especially in the smaller regions where underestimation ranged 25–58 percent; (2) 4–29 percent fewer beds were needed if it was acceptable for demand to exceed supply 18 days/year, versus 4 days/year; and (3) 13–36 percent fewer beds were needed if hospitals within a region could effectively share ICU beds. Conclusions Compared to using yearly averages, analyzing day‐to‐day fluctuations in patient census gives a more accurate picture of ICU bed use. Failing to provide adequate "surge capacity" can lead to demand that frequently and severely exceeds supply.